Investigation of Visible Light Technique - jaein, Afraa jameel Azeez; Amir, Hassan Ayad abd; Ibrahim, AL Hassan Ahmed; Hassan saleh, Abdul Rahman; hassan, Sajad hassan talib (American Journal of Biodiversity, 2025)
The rapid expansion of mobile applications utilizing radio frequencies (RFs) has raised concerns about spectrum limitations, security vulnerabilities, and transmission capacity. This study explores Visible Light Communication (VLC) as an alternative optical wireless communication method, leveraging light in the visible spectrum (375nm–780nm) for secure, high-speed data transmission. Despite its potential, existing research lacks practical implementations addressing range limitations and hardware constraints. This study employs an experimental design to develop and test a VLC system using LEDs and phototransistors. Findings indicate that VLC offers significant security and data rate advantages over RF systems, although challenges such as line-of-sight dependency and transmission range must be optimized. The results suggest that VLC can be a viable solution for indoor wireless communication and intelligent transport systems. These findings have implications for future research and the integration of VLC in smart environments.